Intravenous Immunoglobulin Therapy in Myocarditis - Amir Hossein Mansourabadi (Iranian Journal of Allergy, Asthma and Immunology, 2020)
Myocarditis is an inflammatory disease of the myocardium with lymphocyte infiltration and myocyte necrosis leading to a wide range of clinical presentations including heart failure, arrhythmia, and cardiogenic shock. Infectious and noninfectious agents may trigger the disease. The fact that immunosuppressive drugs are useful in several kinds of autoimmune myocarditis is proof of the autoimmune mechanisms involved in the development of myocarditis. Pathogenic mechanisms in myocardial inflammation are including inflammasome activation followed by myocyte destruction, myocarditis, and pericarditis. Intravenous immunoglobulin (IVIG) is a serum product made up of immunoglobulins, widely used in a variety of diseases. This product is effective in several immune-mediated pathologies. As well as the determined usage of IVIG in Kawasaki disease, IVIG may be useful in several kinds of heart failure including fulminant myocarditis, acute inflammatory cardiomyopathy, Giant Cell Myocarditis, and peripartum cardiomyopathy. Generally, IVIG is used in two different doses of low dose (200 to 400 mg/kg) and high dose (2 g/kg) regimen. The exact therapeutic effects of IVIG are not clear, however over the last decades, our knowledge about its mechanism of function has greatly enhanced. IVIG administration should be based on the accepted protocols of its transfusion. In this review article, we try to provide an overview of the different kinds of myocarditis, pathologic mechanisms and their common treatments and evaluation of the administration of IVIG in these diseases. Furthermore, we will review current protocols using IVIG in each disease individually.